The influence of ethnic background on students' interests in learning literature: a comparison between the Malays and Chinese / Noorul Huda Mohd Dimyati - Mohd Dimyati, Noorul Huda (2004)
The issue of ethnicity has often been discussed in Malaysian education. The performances of different races have often been compared. Questions such as why one group does better than the other and what measures should be taken to close the gap often crop up. This study is a comparative study of two major ethnic groups in Malaysia, the Malays and the Chinese. It attempts to investigate the influence of ethnic background on students' interest in learning literature. Based on the qualitative and quantitative methods a survey was carried out in a secondary school in Pelabohan Klang, Selangor with a sample of Chinese and Malay students and their parents. The findings show that there is no significant difference in students' attitude towards literature based on ethnicity. The responses to all the questions by the students show that none of the items has a statistical significance of 0.05 or better. However, the result shows some difference in attitudes among parents pertaining to the encouragement and motivation of their children. There are two items namely Learning literature is a waste of time and I encourage my children to read English stories and novels that show a statistical significance at 0.04 and 0.01 level.